Phylogenetic shifts of bacterioplankton community composition along the Pearl Estuary: the potential impact of hypoxia and nutrients - Liu, Jiwen; Fu, Bingbing; Yang, Hongmei; Zhao, Meixun; He, Biyan; Zhang, Xiao-Hua (Frontiers in Microbiology, 2015)
The significance of salinity in shaping bacterial communities dwelling in estuarine areas has been well documented. However, the influences of other environmental factors such as dissolved oxygen and nutrients in governing bacterioplankton communities inhabited in local estuarine regions remain elusive. Here, bacterioplankton community structure of surface and bottom waters from eight sites along Pearl Estuary were characterized with 16S rRNA genes pyrosequencing. The bacterioplankton community dendrogram partitioned the samples into three groups, i.e., whole water column of freshwater sites, surface water of saltwater sites and bottom water of saltwater sites. In the saltwater sites, Synechococcus dominated the surface water while Oceanospirillales, SAR11 and SAR406 were prevalent in the bottom water. Betaproteobacteria was abundant in the freshwater sites, with no significant difference between water layers. Moreover, occurrence of phylogenetic shifts in taxa affiliated to the same clade was also detected. Dissolved oxygen explained most of the bacterial community variation in the redundancy analysis targeting only freshwater sites, whereas nutrients and salinity explained most of the variation across all the samples in Pearl Estuary. Methylophilales (mainly PE2 clade) was positively correlated to dissolved oxygen, whereas Rhodocyclales (mainly R.12up clade) was negatively correlated. Moreover, high nutrient inputs to the freshwater area of Pearl Estuary have shifted the bacterial communities towards copiotrophic groups, such as Sphingomonadales. The present study provides a clear outline of bacterioplankton communities in two regions of a subtropical estuary and demonstrates that the overall nutrients and freshwater hypoxia play important roles in determining bacterioplankton compositions